Cytologic features of metastatic epithelioid uterine leiomyosarcoma to the pancreas. Issue 1 (9th September 2022) - Hardy, Naomi L.; Canakis, Andrew; Staats, Paul N.; Darwin, Peter; Legesse, Teklu
Abstract: Although uterine leiomyosarcoma (ULMS) is a rare disease, it accounts for a significant proportion uterine cancer‐related deaths due to frequent metastasis and chemoresistance. The WHO currently recognizes the conventional (spindle), myxoid, and epithelioid variants of ULMS, the latter of which is the rarest, least understood, and cited as clinically more aggressive than the other variants. Descriptions of the histologic features of epithelioid ULMS are extremely limited, and are absent from the cytology literature which has only published descriptions of conventional ULMS or epithelioid variants of other LMS primaries. Therefore, we present a unique case of metastatic epithelioid ULMS to an unusual location, the pancreas, along with its cytologic features on endoscopic ultrasound‐guided fine needle aspiration not previously described including pseudoglandular arrangements, scant cytoplasm, and frequent molding.